2050 China Becoming a Great Modern Socialist Country - Hu, Angang (Understanding Xi Jinping's Governance, 2021)
This book is open access under a CC BY-NC-ND 4.0 license. This book is arranged and developed around the theme of "2050 China," it analyzes the factors and advantages of the Chinese road to socialist modernization, explores and summarizes the development goal and the basic logic of the socialist modernization of China, and further shows the general basis of the primary stage of socialism. According to the report delivered at the 19th Party Congress, and according to the "two-stage" strategic plan, this book looks ahead in detail to the overarching objective and sub-objectives of essentially achieving socialist modernization by 2035, discusses the building of a great modern socialist country in all respects from the perspective of the Party's six-sphere integrated plan of economic, political, cultural, social, ecological civilization, and national defense construction, and provides policy proposals. This book also analyzes the influence and the effect of the socialist modernization with Chinese characteristics on the world and it further presents the third centenary goal. In conclusion, this book is an elaboration of the work of the Institute for Contemporary China Studies, Tsinghua University. It reflects the intellectual innovation in the authors' research on contemporary China, as well as the authors' foresight and predictions about China's future development.